Seismic Liquefaction of Saturated Calcareous Sands: Dynamic Centrifuge Test and Numerical Simulation - Weiqing Lyu; Yong Yuan; Pingshan Chen; Xiaocong Liang; Jiangxu Deng; Chong Li (Applied Sciences, 2022)
Both a dynamic centrifuge test and dynamic finite element analysis were carried out to assess the seismic liquefaction risk of a saturated-calcareous-sand site in a port project in Timor-Leste. Taking the in situ calcareous sands as the model material, two groups of horizontal free-field model tests for medium dense and dense saturated calcareous sands were completed based on the two-stage scaling law theory. Three natural earthquake records with varied peak accelerations were adopted as input motions. The experimental results indicate that the shallower the depth, the lower the relative density, the longer the seismic duration, the larger the peak acceleration, and the more susceptible the saturated site to liquefaction. The sands on site at a depth of five to ten meters is highly risky for liquefaction with the excess pore pressure ratio reaching up to about 1.0 under the seismic peak acceleration of 0.3 g. The risk of liquefaction for site sands is rather small under the seismic peak acceleration of 0.1 g. The study reveals the characteristics of the pore pressure development in sites of varied relative densities under different seismic loadings, which provides a scientific basis for the liquefaction risk assessment of the engineering site.